Lifecycle cost and CO2 emissions of residential heat and electricity prosumers in Finland and the Netherlands. (15th March 2018) - Manrique Delgado, Benjamin; Kotireddy, Rajesh; Cao, Sunliang; Hasan, Ala; Hoes, Pieter-Jan; Hensen, Jan L.M.; Sirén, Kai
Highlights: Multi-objective optim. of heat and electricity prosumers in Netherlands and Finland. The lifecycle costs and CO2 emissions of Dutch and Finnish prosumers are calculated. In Netherlands, use surplus elec. to drive an air-source heat pump and export heat. In Finland, ground-source heat pumps under a similar strategy give optimal results. The results show significant economic potential and emission reductions of prosumers. Abstract: The complexity of finding solutions to reach energy sustainability in the built environment poses a significant challenge. Therefore, there is interest in adequate management of the generation, conversion, storage, use and exchange of heat and electricity. The novelty of this study exists in presenting and comparing multiobjective optimizations for operational CO2 emissions and lifecycle costs (LCC) of heat and electricity prosumers in the Netherlands and Finland, with and without net-metering. The premise relies on using surplus electricity to drive heat pumps for heat export instead of exporting surplus electricity. In the Netherlands, the calculated cost optimal solutions consist of using surplus electricity to drive an air source heat pump and export heat, with CO2 emissions and ΔLCC of −41.1 kgCO2 eq/(m 2 a) and €−69.7/m 2 (22% lower), respectively. In Finland, the heat export strategy allows a ΔLCC of €−24.5/m 2 (8% lower), with CO2 emissions reduced by −32.5 kgCO2 eq/(m 2 a). Without net-metering, the ΔLCC of the energy system rises to €−4/m 2 in the Netherlands; with net metering, the ΔLCC lowers to €−65.6/m 2 in Finland. The results indicate the potential for significant economic and emission reductions in heat and electricity prosumers.